Faktor-faktor Berpengaruh Terhadap Kinerja Manajer Proyek Konstruksi dengan Pendekatan Structural Equation Modeling - Sahadi, Sahadi; Wibowo, M. Agung (Department of Civil Engineering, Diponegoro University, 2010)
All activities depend on the human resources who carry out those activities. Therefore, attention and amphasis on the development of human resources are a strategic and an urgent need. There are several resources that must be controlled by a contractors, which include the human resources, and they play the most important role among other resources because all the aspects of construction activity and the use of other resources is always controlled by humans such as the use of financial, material, aquipment and work method resources, and so on. This study aims to find out the influence of leadership, organization climate, organization culture, communication climate, trust, work motivation, work experience, reward/salary, and work satisfaction on the performance of construction project managers using structural equation modeling (SEM) approach. The result of study indicate that relationship, organization climate, organization culture, communication climate, trust, work motivation, work experience, reward/salary and work satisfaction have a positive influence on the performance. Variables that have dominant influence on the performance of construction project managers are reward and work experience. Keywords : Performance of project managers, Leadership, Organization culture, Work motivation, SEM. Â Abstrak Â Segala aktifitas tergantung dari sumber daya manusia yang melaksanakan, untuk itu perhatian dan peneanan terhadap pengembangan sumber daya manusia merupakan hal yang stategis dan mendesak. Beberapa sumber daya yang harus dikelola oleh kontraktor, sumber daya manusia adalah sumber daya yang mempunyai peran paling besar karena setiap bagian kegiatan konstruksi atau penggunaan-penggunaan sumber daya lain akan selalu dikendalikan oleh manusia, misalnya penggunaan sumber daya keuangan, sumber daya material, sumber daya peralatan, penggunaan metode kerja dan seterusnya. Tujuan penelitian ini adalah untuk mengetahui pengaruh kepemimpinan, iklim organisasi, budaya organisasi, iklim komunikasi, kepercayaan, motivasi kerja, pengalaman kerja, imbalan/gaji, dan kepuasan terhadap kinerja pada manajer proyek kostruksi dengan pendekatan structural equation modeling (SEM). Hasil penelitian menunjukkan bahwa kepemimpinan, iklim organisasi, budaya organisasi, iklim komunikasi, kepercayaan, motivasi kerja, pengalaman kerja, imbalan/gaji, dan kepuasan berpengaruh positif terhadap kinerja. Sedangkan variable yang berpengaruh dominan terhadap kinerja manajer proyek konstruksi adalah imbalan dan pengalaman kerja. Kata-kata Kunci : Kinerja manajer proyek, kepemimpinan budaya organisasi, motivasi kerja, SEM.